Pengaruh Penggunaan Lms Webcode Berbasis Moodle Terintegrasi Pbl Terhadap Hasil Belajar Murid Pada Elemen Pemrograman Web - Faniah Iftitakhul Kamilah; Martini Dwi Endah Susanti (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Student learning outcomes in the Web Programming unit at the vocational high school (SMK) level remain a challenge during the implementation of the kurikulum Merdeka (Independent Curriculum), particularly regarding the mastery of cognitive concepts and practical psychomotor skills. This study aimed to analyze the impact of using the Moodle-based "WebCode" Learning Management System (LMS)—integrated with the Problem-Based Learning (PBL) model—on the learning outcomes of Grade XI Software Engineering (RPL) students at SMK Krian 1 Sidoarjo in the Web Programming unit. A quasi-experimental design—specifically a non-equivalent control group design—was employed. Learning outcome data were collected using cognitive test instruments and psychomotor performance assessment sheets, which were validated by experts; the instruments achieved a validity score of 95%, falling into the "Highly Valid" category. Inferential analysis using the Independent Sample T-Test revealed a cognitive t-value of 7.975 and a psychomotor t-value of 3.339 (with p < 0.05), indicating a significant difference in learning outcomes between the experimental class (using the PBL-integrated WebCode LMS) and the control class (using conventional methods). The magnitude of improvement in learning outcomes was measured using the N-Gain test, yielding an average score of 0.729 (high category) for the cognitive domain and 0.400 (medium category) for the psychomotor domain. These results indicate that the PBL-integrated, Moodle-based WebCode LMS is capable of significantly and effectively improving student learning outcomes in the Web Programming unit.